ANALYSIS OF FINANCIAL PERFORMANCE IN THE GOVERNMENT OF NORTH SULAWESI - Korompot, Riska; Warongan, Jessy (Universitas Sam Ratulangi, 2017)
The objective of this research was to determine the financial performance of North Sulawesi Provincial Government and was measured from the Independence Ratio, Effectiveness Ratio, Degree of Fiscal Decentralization Ratio, Harmony Ratio, and Growth Ratio. The results showed that the Independence ratio of North Sulawesi Province in 6 years from 2010-2015 has increased and included in the category of Participatory which means it is quite independent and has reduced the level of dependence on external parties and manage the existing funds such as Domestic Revenue as well as describe that the people of North Sulawesi is quite prosperous because it is able to participate in tax payments which is one of the largest regional income. The Effectiveness Ratio of Domestic Revenue shows effective criteria to the Regional Financial Performance, because based on the effectiveness ratio of Domestic Revenue in 6 years of research only last 2 years namely 2014 and 2015 which include in the category of Not Effective which means decreasing on the performance of local government of North Sulawesi province. The Decentralization Degrees for Government of North Sulawesi Province shows that they still has not fully fulfilled the total revenue with they own-source revenue. The Harmony Ratio represents more realization of operating expenditures than capital expenditures, this is not so good especially for developing regions such as North Sulawesi Province. The Growth Ratio shows an unstable number from 2010 to 2015. The instability is caused by the implementation of money follows functions which are considered not optimal yet, so the work that must be done by some Regional Work Unit at the same time according to expertise and the division is not going well.Keywords : regional financial performance, APBD